2020
DOI: 10.1093/reseval/rvaa019
|View full text |Cite
|
Sign up to set email alerts
|

The use of an impact framework to evaluate the impact of research on policy and practice: Screening questionnaires for intellectual disability

Abstract: There is an increasing emphasis on the importance of research having an impact on policy and practice. This can be more difficult to evidence in intellectual disability services because of the wide range of stakeholders involved. We evaluated whether an impact questionnaire covering: knowledge production, capacity building, informing policy and practice, social and economic benefits could successfully be used to evaluate the impact of research into and use of two screening questionnaires: the Learning Disabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 82 publications
(105 reference statements)
2
11
0
Order By: Relevance
“…While there is the possibility that those who are identified as likely to meet the criteria for learning disability may feel stigmatised, as outlined previously, research suggests that this was identified as a potential psychological risk by less than 1 in 5 parents, service users, and professionals. The LDSQ has also been identified as a means by which the issue of prisoners being ashamed to highlight their difficulties can be addressed (McKenzie et al 2021).…”
Section: The Risks Both Physical and Psychological Should Be Less Tha...mentioning
confidence: 99%
See 1 more Smart Citation
“…While there is the possibility that those who are identified as likely to meet the criteria for learning disability may feel stigmatised, as outlined previously, research suggests that this was identified as a potential psychological risk by less than 1 in 5 parents, service users, and professionals. The LDSQ has also been identified as a means by which the issue of prisoners being ashamed to highlight their difficulties can be addressed (McKenzie et al 2021).…”
Section: The Risks Both Physical and Psychological Should Be Less Tha...mentioning
confidence: 99%
“…Overall, research suggests that use of the CAIDS-Q and LDSQ has few disadvantages and many advantages (McKenzie et al 2021). The most obvious advantage and key purpose of the screening tools is that they accurately identify people who are likely to meet the criteria for learning disability.…”
Section: The Costs Should Be Balanced Against the Benefitsmentioning
confidence: 99%
“…Those with a percentage score that falls below the relevant cut-off are indicated as likely to meet the criteria for intellectual disability. Like the CAIDS-Q, the LDSQ has also been used in different settings and found to demonstrate good psychometric properties (see McKenzie et al, 2021). A study which validated the LDSQ against the updated Weschler Adult Intelligence Scale (Wechsler, 2010) found it to have sensitivity and specificity values of 91.5 % and 91.7 % respectively.…”
Section: Materials and Designmentioning
confidence: 99%
“…The sensitivity, specificity, positive and negative predictive values, for the CAIDS-Q and LDSQ. to have an intellectual disability, prioritise assessments, and reduce waiting times for assessment (see McKenzie et al, 2021). The CAIDS-Q has also been highlighted as a helpful tool for professionals who are part of neurodevelopmental screening, assessment, and diagnosis pathways, such as teachers, nurses, and paediatricians (Rutherford et al, 2021).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation